Photoactivated riboflavin inhibits planktonic and biofilm growth of Candida albicans and non-albicans Candida species - Farah, Nuratiqah; Lim, Chee Woei; Chin, Voon Kin; Chong, Pei Pei; Basir, Rusliza; Yeo, Wendy Wai Yeng; Tay, Sun Tee; Choo, Sulin; Lee, Tze Yan (Academic Press, 2024)
Fungal infections caused by Candida species pose a serious threat to humankind. Antibiotics abuse and the ability of Candida species to form biofilm have escalated the emergence of drug resistance in clinical settings and hence, rendered it more difficult to treat Candida-related diseases. Lethal effects of Candida infection are often due to inefficacy of antimicrobial treatments and failure of host immune response to clear infections. Previous studies have shown that a combination of riboflavin with UVA (riboflavin/UVA) light demonstrate candidacidal activity albeit its mechanism of actions remain elusive. Thus, this study sought to investigate antifungal and antibiofilm properties by combining riboflavin with UVA against Candida albicans and non-albicans Candida species. The MIC20 for the fluconazole and riboflavin/UVA against the Candida species tested was within the range of 0.125–2 μg/mL while the SMIC50 was 32 μg/mL. Present findings indicate that the inhibitory activities exerted by riboflavin/UVA towards planktonic cells are slightly less effective as compared to controls. However, the efficacy of the combination towards Candida species biofilms showed otherwise. Inhibitory effects exerted by riboflavin/UVA towards most of the tested Candida species biofilms points towards a variation in mode of action that could make it an ideal alternative therapeutic for biofilm-related infections.